Shelf space allocation problem under carbon tax and emission trading policies. (20th September 2018) - Yu, Vincent F.; Maglasang, Renan; Tsao, Yu-Chung
Abstract: This study formulates a mixed integer nonlinear programming (MINLP) model for the shelf space allocation problem (SSAP) under two common environmental policies: the Carbon Tax System and the Emission Trading System. For each system, the impact on profitability and the opportunities for emission cuts are presented. Via numerical experiments we specifically explore the impact of a fixed carbon tax, emission allowances, and emission price on two of the most important in-store management decisions in retail: shelf space capacity and product allocation decisions. Real-life retail data of four product categories are tested and solved to optimality using COUENNE. Then, we analyze optimal solutions to gain important insights for the benefit of both retailers and governmental decision makers.